Optimizing standalone dual PV systems with four-port converter technology - Sha, Sharma; Kalayanasundaram, Rajambal (Institute of Advanced Engineering and Science, 2025)
This paper analyses the four-port converter (FPC) based PV system. The discussed FPC is developed for hybrid energy sources (HES) with the merits of a single converting stage, fewer switches, and simple topology. By tapping two source ports from the midway of its two switching legs, the FPC presented in this work is developed from the basic full bridge converter (FBC). The pulses are produced using the phase angle control with pulse width modulation (PPAS) technique. Different modes of operation of the FPC are analyzed elaborately to give an insight into its topology. To efficiently manage power distribution among the ports and regulate their voltage, two key control variables have been utilized: duty ratio and phase angle. An in-depth presentation is provided on the design and modeling of a four-port converter. It provides autonomous management of power allocation among terminals and regulation of load voltage. Finally, simulated key waveforms of the FPC and simulation results to demonstrate the decoupled regulation of power sharing and load voltage of a PV system under varying input and output conditions are presented. The experimental prototype of the four-port converter results is discussed and presented in detail.